Traditional Cultures versus Next Generation Sequencing for Suspected Orthopedic Infection: Experience Gained from a Reference Centre - Sara Giordana Rimoldi; Davide Brioschi; Daniele Curreli; Federica Salari; Cristina Pagani; Alessandro Tamoni; Concetta Longobardi; Raffaella Bosari; Alberto Rizzo; Simona Landonio; Massimo Coen; Matteo Passerini; et al. (MDPI AG, 2023)
(Background) The diagnosis and the antimicrobial treatment of orthopedic infection are challenging, especially in cases with culture-negative results. New molecular methods, such as next-generation sequencing (NGS), promise to overcome some limitations of the standard culture, such as the detection of difficult-to-grow bacteria. However, data are scarce regarding the impact of molecular techniques in real-life scenarios. (Methods) We included cases of suspected orthopedic infection treated with surgery from May 2021 to September 2023. We combined traditional cultures with NGS. For NGS, we performed a metagenomic analysis of ribosomal 16s, and we queried dedicated taxonomic libraries to identify the species. To avoid false positive results, we set a cut-off of 1000 counts of the percentage of frequency of reads. (Results) We included 49 patients in our study. Our results show the presence of bacteria in 36/49 (73%) and 29/49 (59%) cases studied with NGS and traditional cultures, respectively. The concordance rate was 61%. Among the 19/49 discordant cases, in 11/19 cases, cultures were negative and NGS positive; in 4/19, cultures were positive and NGS negative; and in the remaining 4/19, different species were detected by traditional cultures and NGS. (Conclusions) Difficult-to-grow microorganisms, such as slow-growing anaerobic bacteria, were better detected by NGS compared to traditional culture in our study. However, more data to distinguish between true pathogens and contaminants are needed. NGS can be an additional tool to be used for the diagnosis of orthopedic infections and the choice of appropriate antimicrobial therapy.